Unveiling the root causes and results of illegitimate tasks: A systematic literature review - Iqbal Saleha; Ismail Rozmi; Badayai Abdul Rahman bin Ahmad; Sitinjak Charli; Ober Józef; Kochmańska Anna (Journal of Economics and Management)
Aim/purpose – Employees are expected to perform duties consistent with their professional roles. However, they are often required to undertake tasks they perceive as unreasonable or unnecessary. The concept of illegitimate tasks has garnered increasing attention since its introduction. Illegitimate tasks have been found to account for unique variations in well-being and stress. A systematic narrative review of the literature on illegitimate tasks is necessary since the relevant literature is still in its infancy.